Conversão de energia em sistemas fotovoltaicos conectados à rede elétrica: avaliação da eficiência de um sistema monofásico de dois estágios - Melquíades, Antônia Daiara de Almeida (Universidade Federal Rural do Semi-Árido, 2019)
This work aims to analyze the process of energy conversion in photovoltaic systems connected to the grid (SFCR) and its relevance to the micro and distributed minigeration. The concepts used address issues such as power generation and the types of schemes most used, with emphasis on photovoltaic systems. In this way, the research is theoretically based on Barreto (2014), and Rocha (2015), among others. In order to do so, the object of study is the degree of efficiency of this type of system in function of the factors that influence the losses associated to the process of energy conversion, where its character is proved through the comparative analysis between values of generated power and power delivered to the power grid. The data are extracted by means of graphs of a monophasic photovoltaic system connected to the grid, designed and simulated in environment (Software for Power Electronics Simulation - PSIM). The results of the study propose an alternative for the generation of clean and renewable electricity through the use of the solar resource, aiming at a possible reduction of the use of hydroelectric plants, which may allow a minimization of the environmental and social impacts caused by the use of this type of system.
Energy conversion in photovoltaic systems connected to the electrical network: evaluation of the efficiency of a single-phase two-stage system
Monografia
Keywords: Sistemas fotovoltaicos; Rede elétrica; Conversão de energia; Energia renovável; Photovoltaic systems; Electrical network; Energy conversion; Renewable energy; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA